A ROS-mediated lysosomal–mitochondrial pathway is induced by ginsenoside Rh2 in hepatoma HepG2 cells. Issue 12 (9th October 2015) - Chen, Fang; Deng, ZeYuan; Xiong, ZengXing; Zhang, Bing; Yang, JianYuan; Hu, JiangNing
Abstract : ROS/lysosomal/mitochondrial pathway was involved in the apoptotic response induced by GRh2 in hepatoma HepG2 cells. Abstract : Ginsenoside Rh2 (GRh2), isolated from Panax ginseng C. A. Meyer, has been proven as an anticancer compound both in vitro and in vivo . In the present study, we investigated the role of the lysosomes during the apoptosis of HepG2 cells induced by GRh2. The results showed that GRh2 significantly induced intracellular reactive oxygen species (ROS) generation in the HepG2 cells, which consequently resulted in early lysosomal membrane permeabilization with the release of cathepsin B (Cat B) to the cytosol. Western blot analysis showed that the released Cat B in the cytosol contributed to Bid cleavage. Subsequently mitochondrial damage was observed in the HepG2 cells. Interestingly, when the HepG2 cells were pre-treated with N -Acetyl-l -Cysteine (NAC) for 1 h, which inhibited ROS generation before being exposed to GRh2, the permeabilization of lysosomal membranes and the levels of Cat B in the cytosol were down-regulated. Moreover, mitochondrial damage was alleviated when the HepG2 cells were pre-treated with leupeptin (Leu). From the above results, it could be concluded that GRh2 induced apoptosis of the HepG2 cells through accumulation of ROS and activation of the lysosomal–mitochondrial apoptotic pathway involving the release of Cat B.